Problemas que plantea la descentralización productiva: los contratos para obra o servicio específico y la causa objetiva de contratación - Jiménez Silva, Carlos (2021)
Through this research work, it is intended to show that the institution of productive decentralization of the company is often used as an objective cause of hiring for a specific work or specific service, thereby making the employment relationship of the workers precariously, for which a normative precision is necessary